Advantages and Challenges of Cardiovascular and Lymphatic Studies in Zebrafish Research - Santoro, Massimo M.; Beltrame, Monica; Panáková, Daniela; Siekmann, Arndt F.; Tiso, Natascia; Venero Galanternik, Marina; Jung, Hyun Min; Weinstein, Brant M. (Frontiers in Cell and Developmental Biology, 2019)
Since its introduction, the zebrafish has provided an important reference system to model and study cardiovascular development as well as lymphangiogenesis in vertebrates. A scientific workshop held at the 2018 European Zebrafish Principal Investigators Meeting in Trento, Italy and chaired by Massimo Santoro, focused on the most recent methods and studies on cardiac, vascular and lymphatic development. Daniela Panáková and Natascia Tiso described new molecular mechanisms and signaling pathways involved in cardiac differentiation and disease. Arndt Siekmann and Wiebke Herzog discussed novel roles for Wnt and VEGF signaling in brain angiogenesis. In addition, Brant Weinstein’s lab presented data concerning the discovery of endothelium-derived macrophage-like perivascular cells in the zebrafish brain, while Monica Beltrame’s studies refined the role of Sox transcription factors in vascular and lymphatic development. In this article, we will summarize the details of these recent discoveries in support of the overall value of the zebrafish model system not only to study normal development, but also associated disease states.